A Fuzzy Decision Support System for irrigation and water conservation in agriculture. (January 2015) - Giusti, E.; Marsili-Libelli, S.
Abstract: Since agriculture is the major water consumer, web services have been developed to provide the farmers with considerate irrigation suggestions. This study improves an existing irrigation web service, based on the IRRINET model, by describing a protocol for the field implementation of a fully automated irrigation system. We demonstrate a Fuzzy Decision Support System to improve the irrigation, given the information on the crop and site characteristics. It combines a predictive model of soil moisture and an inference system computing the most appropriate irrigation action to keep this above a prescribed "safe" level. Three crops were used for testing the system: corn, kiwi, and potato. This Fuzzy Decision Support System (FDSS) favourably compared with an existing agricultural model and data-base (IRRINET). The sensitivity of the FDSS was tested with random rainfall and also in this extended case the water saving was confirmed. Graphical abstract: Highlights: We describe a Fuzzy Decision Support System to decide the irrigation based on soil moisture and rain forecast. Its rules are easily editable and can be specialized for each crop and agricultural condition. The system provided improved irrigation suggestions in terms of timing and water saving.